Tujuan pendidikan nasional dalam perspektif Pancasila - Rukiyati, Rukiyati (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2019)
The educational objectives contained in Act Number 20 of 2003 concerning theNational Education System in Indonesia is to develop multidimensional and holistichuman nature. The relationship between the components of the goal as an integral wholeand there is a hierarchy of values in the achievement of goals. The natural aspects ofhumanity are seen as a potential that needs to be developed so that humans reach personalqualities as human beings who have noble character, both when dealing with the Creatorin terms of faith and piety (believe in one God) and when dealing with fellow creatures inworld life (humanity, unity, democracy, and social justice). The purpose of education isactually the values of Pancasila in another formulation because, in fact, the foundation ofIndonesia's national education philosophy is Pancasila.